Limited therapeutic efficacy of pioglitazone on progression of hepatic fibrosis in rats. Issue 7 (16th February 2006) - Leclercq, I A; Sempoux, C; Stärkel, P; Horsmans, Y
Abstract : Aim: Peroxisome proliferator activated receptor γ (PPARγ) agonists have been shown to prevent hepatic fibrosis in rodents. We evaluated the therapeutic antifibrotic potential of the PPARγ agonist pioglitazone on established hepatic fibrosis. Methods: Repeated injections of carbon tetrachloride (CCl4 ), a choline deficient diet, or bile duct ligation (BDL) were used to induce hepatic fibrosis in rats. Pioglitazone treatment was introduced at various time points. Therapeutic efficacy was assessed by comparison of the severity of hepatic fibrosis in pioglitazone treated versus untreated fibrotic controls. Results: When introduced after two weeks of CCl4, pioglitazone reduced hepatic fibrosis, OH proline content, hepatic mRNA expression of collagen type I, and profibrotic genes, as well as the number of activated α smooth muscle actin positive hepatic stellate cells, compared with rats receiving CCl4 only, with no significant change in necroinflammation. When pioglitazone treatment was initiated after five weeks of CCl4, no antifibrotic effect was observed. Similarly, pioglitazone was associated with a reduced severity of fibrosis induced by a choline deficient diet when introduced early, while delayed treatment with pioglitazone remained ineffective. In contrast, pioglitazone failed to interrupt progression of fibrosis due to BDL, irrespective of the timing of its administration. Conclusion: In rats, the therapeutic antifibrotic efficacy of pioglitazone is limited and dependent on the type of injury, duration of disease, and/or the severity of fibrosis at the time of initiation of treatment.